Integral industrialization of the artichoke in nutrional pasta and for balanced food. - García Zapata, Teonila (2008)
A study of descriptive and experimental type was made, with the intention of processing the artichoke for the paste obtaining, as much for the human feeding, as for medicinal use and articles of beauty, as well as the use of the remainders for the balanced food elaboration, that entail to cause creation of companies dedicated from the production of the artichoke to their transformation and commercialization, to satisfy the internal market and for the export, of such form that is generated a chain of highly profitable value for the producing agricultural zones of this vegetable. Taking the possibility of the industrialization as an lens on the basis of the economic performance that from it stems.